Electrochemically Activated Conductive Ni-Based MOFs for Non-enzymatic Sensors Toward Long-Term Glucose Monitoring - Chen, Yating; Tian, Yulan; Zhu, Ping; Du, Liping; Chen, Wei; Wu, Chunsheng (Frontiers in Chemistry, 2020)
Continuous intensive monitoring of glucose is one of the most important approaches in recovering the quality of life of diabetic patients. One challenge for electrochemical enzymatic glucose sensors is their short lifespan for continuous glucose monitoring. Therefore, it is of great significance to develop non-enzymatic glucose sensors as an alternative approach for long-term glucose monitoring. This study presented a highly sensitive and selective electrochemical non-enzymatic glucose sensor using the electrochemically activated conductive Ni3(2,3,6,7,10,11-hexaiminotriphenylene)2 MOFs as sensing materials. The morphology and structure of the MOFs were investigated by scanning SEM and FTIR, respectively. The performance of the activated electrode toward the electrooxidation of glucose in alkaline solution was evaluated with cyclic voltammetry technology in the potential range from 0.2 V to 0.6 V. The electrochemical activated Ni-MOFs exhibited obvious anodic (0.46 V) and cathodic peaks (0.37 V) in the 0.1 M NaOH solution due to the Ni(II)/Ni(III) transfer. A linear relationship between the glucose concentrations (ranging from 0 to 10 mM) and anodic peak currents with R2 = 0.954 was obtained. It was found that the diffusion of glucose was the limiting step in the electrochemical reaction. The sensor exhibited good selectivity toward glucose in the presence of 10-folds uric acid and ascorbic acid. Moreover, this sensor showed good long-term stability for continuous glucose monitoring. The good selectivity, stability, and rapid response of this sensor suggests that it could have potential applications in long-term non-enzymatic blood glucose monitoring.